Four new taraxastane-type triterpenoic acids from Cirsium setosum. Issue 11 (1st November 2016) - Luan, Na; Wei, Wen-Di; Wang, Ali; Wu, Xiu-Li; Qi, Yan; Li, Jin-Jie; Zheng, Jian-Quan; Shang, Xiao-Ya
Abstract: Four new taraxastane-type triterpenoids acids 3 β, 22 α -dihydroxy-20-taraxasten-30-oic acid (1 ), 3 β -hydroxy-22-oxo-20-taraxasten-30-oic acid (2 ), 3-oxo-22 α -hydroxy-20- taraxasten-30-oic acid (3 ), and 3β, 19β-dihydroxy-20-taraxasten-30-oic acid (4 ) were isolated and characterized from Cirsium setosum (Willd.) MB. Their structures were determined by the combination of 1D and 2D NMR experiments ( 1 H- 1 HCOSY, HSQC, HMBC and ROESY) and mass spectrometry. Compound2 exhibited potent selective cytotoxicity against human ovarian cancer cell line A2780 with an IC50 value of 3.9 μM.